2010
DOI: 10.2165/11534530-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity – Exercise-Induced Response of Peripheral Brain-Derived Neurotrophic Factor

Abstract: Exercise is known to induce a cascade of molecular and cellular processes that support brain plasticity. Brain-derived neurotrophic factor (BDNF) is an essential neurotrophin that is also intimately connected with central and peripheral molecular processes of energy metabolism and homeostasis, and could play a crucial role in these induced mechanisms. This review provides an overview of the current knowledge on the effects of acute exercise and/or training on BDNF in healthy subjects and in persons with a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
580
4
29

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(645 citation statements)
references
References 122 publications
32
580
4
29
Order By: Relevance
“…68 There remains some controversy as to whether lower or higher levels of BDNF levels in the periphery are protective. It has been suggested that lower levels of BDNF in people with higher fitness levels may reflect more effective BDNF clearance in the periphery of these individuals (see review by Knaepen and colleagues 69 ), furthermore the form of BDNF being investigated (i.e. pro-BDNF vs total BDNF) may also be a determining factor in terms of the effect of BDNF on AD risk.…”
Section: Exercise May Increase Levels Of Growth Factors and Neurotranmentioning
confidence: 99%
“…68 There remains some controversy as to whether lower or higher levels of BDNF levels in the periphery are protective. It has been suggested that lower levels of BDNF in people with higher fitness levels may reflect more effective BDNF clearance in the periphery of these individuals (see review by Knaepen and colleagues 69 ), furthermore the form of BDNF being investigated (i.e. pro-BDNF vs total BDNF) may also be a determining factor in terms of the effect of BDNF on AD risk.…”
Section: Exercise May Increase Levels Of Growth Factors and Neurotranmentioning
confidence: 99%
“…It is well accepted that motor recovery after stroke is achieved through cortical reorganization, in which the brain and central nervous system (CNS) adapt in response to environmental and behavioral change to acquire novel information by modifying neural connectivity and function (Knaepen, Goekint, Heyman, & Meeusen, 2010;Mang, Campbell, Ross, & Boyd, 2013). Although the exact mechanism for cortical reorganization is not known, neurotrophins are thought to play a major role by enabling neuronal survival, potentiation, and differentiation; promoting dendritic growth and remodeling; and promoting synaptic plasticity (Lin & Kuo, 2013;Voss, Nagamatsu, Liu-Ambrose, & Kramer, 2011).…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27]. Other factors such as electrical stimulation (transcranial direct current stimulation), habitual exercise, pharmacological agents, psycho-/behavioral therapy, stress as well as environmental factors also affect neurometaplasticity [28][29][30][31][32][33][34][35]. These factors affect neurometaplasticity by indirect influence on neurotransmitters, receptors, transporters, genome and epigenome of brain cells [29,30].…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%
“…Other factors such as electrical stimulation (transcranial direct current stimulation), habitual exercise, pharmacological agents, psycho-/behavioral therapy, stress as well as environmental factors also affect neurometaplasticity [28][29][30][31][32][33][34][35]. These factors affect neurometaplasticity by indirect influence on neurotransmitters, receptors, transporters, genome and epigenome of brain cells [29,30]. The receptors implicated in LTP and LTD include N-methyl-D-aspartate receptor (NMDAR), metabotropic glutamate receptors (mGluRs), endocannabinoid receptors, ion channel receptors (e.g.…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%